A prática pedagógica em musicalização inclusiva para alunos surdos no Conservatório Estadual de Música Cora Pavan Capparelli : as relações de ensino e aprendizagem mediadas por intérprete - Silva, Gislaine Sousa (2015)
This research deals with the pedagogical music practice mediated by the sign language interpreter in an inclusive context for music teaching with deaf students. The research aimed at understanding how such pedagogical music practice was undertaken within a specialist music school in Uberlândia MG, the State Conservatory of Music Cora Pavan Capparelli. The more specific aims involved understanding the educational reality of this inclusive musicalization process, verifying the teaching-learning relations established by the teachers, the deaf students and the sign language interpreter in the classroom; thus, it was finding out different perceptions of the teachers in relation to the deaf students included in the music lesson. The interview with the sign language interpreter attempted to understand her perception on the pedagogical practice of the music teachers. In such context, it was possible to identify inherent challenges/problems from the process of teaching music for deaf students in a specialist music school. The reseach study adopted a qualitative approach. The method employed was a case study and the procedures for data collection were based on semi-structured interviews and observations. The theoretical framework was underpinned by the following authors: Tardiff (teaching skills), Ann Darrow (methodological adaptation for music teaching for deaf students) and Evelyn Glennie (the individual deaf and music). The results suggest that there are inherent in the triad teacher - sign language interpreter - deaf student, pedagogical challenges to be overcome by the teachers without a consistent formation/training in the inclusive musicalization lessons, and issues involving to the implementation of laws that underpin this music teaching modality in the Conservatory.